(untitled) (Medico Legal Update, 2020)
The isolation of active plants compounds lead to discover a several drugs derived directly from plants. In the current study, the Glucokinin was isolated and purified from the methanol leave extract of medicinal plant Bauhinia variegate, the attempts to identified and characterized it’s functional groups by the HPLC and FTIR spectroscopy was worked in this study. By using FT-IR spectroscopic the Glucokinin shown different functional groups. The FTIR spectrum of the purified material, Glucokinin from the methanol leaf extract of B. variegata indicate the presence of different functional groups. The peak near 1650 cm-1 is the amide I band.